An approach of steel plate hybrid bonding technique to externally bonded fibre-reinforced polymer strengthening system - Xue Zhang; Zhimin Wu; Ye Cheng (International Journal of Distributed Sensor Networks)
The strengthening efficiency of externally bonded fibre-reinforced polymer to concrete structure is usually limited owing to the unexpected debonding of fibre-reinforced polymer laminates. In this study, a new steel plate hybrid bonding technique was developed to supply additional anchorage for traditional externally bonded fibre-reinforced polymer strengthening system. With this approach, the fibre-reinforced polymer debonding can be effectively prevented. Moreover, the stress concentration, which probably results in a premature fracture of fibre-reinforced polymer laminates as that performed for available hybrid bonding anchorage techniques, can be eliminated by introducing a steel plate between the mechanical fasteners and fibre-reinforced polymer strips. To verify the effect of this new method, 21 carbon fibre–reinforced polymer–strengthened beams were studied on the flexural behaviours. Test results showed that, compared to available hybrid bonding anchorage techniques, steel plate hybrid bonding is more capable of making the full use of fibre-reinforced polymer laminates and further enhance the ultimate capacity and ductility of externally bonded fibre-reinforced polymer–strengthened beams. Based on the experimental results, the effect of interfacial treatment, ply of carbon fibre–reinforced polymer and mechanical fastener spacing on the failure mode and ultimate load ratio were discussed. Eventually, a simplified analytical procedure was proposed and verified to estimate the flexural resistance of steel plate hybrid bonding – fibre-reinforced polymer–strengthened beam.